A Note on Medical Sciences, Good Death and Good Dying - Kwon, Ik-Whan G.; Kim, Sung-Ho (British Journal of Healthcare and Medical Research, 2026)
This Note explores the distinction between “good death” and “good dying” in relation to advancement of medical sciences. Although advances in medical science have extended life expectancy, living longer does not necessarily ensure dignity, comfort, and/or psychological well-being at the end of life. We take a position that death is an event, whereas dying is a process shaped by symptom management, communication, family presence, psycho-social support, and ethical care. It further highlights the paradox that medical progress may prolong life while simultaneously widening the gap between longevity and quality of life, particularly among socially isolated older population. Accordingly, this paper calls for attention to palliative care, end-of-life, and dignity-based practice to reduce suffering in the final stage of life.